The Casting of Julian the Apostate 'in the Likeness' of Alexander the Great: a Topos in Antique Historiography and its Modern Echoes - Smith, Rowland B. E. (Histos, 2011)
Parallels between Julian the Apostate and Alexander the Great were drawn repeatedly in antiquity. Although the comparison instantiates a familiar topos in the repertoire of Roman imperial panegyrists and historiographers, in Julian’s case a unique complexity attaches to the 'Alexander comparison' on several counts. Close reading discloses lines of influence and reaction holding between the earlier and later testimonies, and what some of them postulate reflects an awareness of observations made about Alexander in Julian’s writings that indicate a strong interest in him on the emperor’s own part. Moreover, the image of Julian as an obsessive 'Alexander-emulator' transmitted in one strand of the ancient tradition has a modern counterpart in some scholarship which ascribes to him a deepening psychological inclination to identify with, or to rival, Alexander. This paper aims both to explicate the formation and development of the theme of Julian’s 'likeness to Alexander' as an antique literary construct, and to review the modern representation of him as a passionate 'Alexander-emulator', arranged in four sections: I. Introduction; II. Precedents and parallels: the 'likeness to Alexander' theme as a literary topos; III. The passage of the Julian–Alexander comparison from rhetoric to historiography in the external testimonies: (i) Libanius; (ii) Ammianus; (iii) the Christian testimonies (Gregory Nazianzen, Philostorgius and Socrates Scholasticus); IV. Alexander’s image in Julian’s writings: the hypothesis of emulation reviewed.